Reconstruction of Civil Liability in “Pay-on-Site” Payment Schemes: An Analysis of Consumer Protection in the Era of Electronic Commerce - Oktavia Purnamasari Sigalingging; Surya Perdana; Farid Wajdi (PT. Global Research Collaboration, 2026)
The rapid development of electronic commerce has transformed conventional transaction mechanisms, including the emergence of the cash on delivery (COD) payment scheme as an alternative perceived to reduce consumer risk. However, COD transactions introduce complex legal challenges, particularly in determining the allocation of civil liability among multiple actors involved, such as sellers, logistics providers, and digital platforms. This study aims to analyze the regulation and implementation of civil liability in COD transactions and to propose a reconstructed legal framework to enhance consumer protection. This research employs a normative juridical approach supported by qualitative analysis of statutory regulations, legal doctrines, and relevant literature. The findings reveal that existing legal frameworks in Indonesia remain fragmented and insufficient to address the hybrid nature of COD transactions, where contractual agreement, delivery, and payment occur simultaneously. This condition creates ambiguity in liability allocation and weakens consumer protection, particularly under traditional fault-based liability systems that impose a heavy burden of proof on consumers. This study offers a novel contribution by conceptualizing COD transactions as a hybrid legal model and introducing the concept of a multi-actor liability structure, which leads to a liability gap due to overlapping and unclear responsibilities. To address this issue, the research proposes a reconstruction of civil liability based on strict liability principles combined with enhanced platform accountability. The study concludes that such a reconstruction is necessary to improve legal certainty, ensure fair risk distribution, and strengthen consumer protection in the evolving landscape of electronic commerce.